A class of auxetic three-dimensional lattices. (June 2016) - Cabras, Luigi; Brun, Michele
Abstract: We propose a class of auxetic three-dimensional lattice structures. The elastic microstructure can be designed to have an omnidirectional Poisson's ratio arbitrarily close to the stability limit of −1. The cubic behaviour of the periodic system has been fully characterized; the minimum and maximum Poisson's ratio and the associated principal directions are given as a function of the microstructural parameters. The initial microstructure is then modified into a body-centred cubic system that can achieve Poisson's ratio lower than −1 and that can also behave as an isotropic three-dimensional auxetic structure. Graphical abstract: